STROKES TO THE PSYCHOLOGICAL PORTRAIT OF ZOSIMA IN THE NOVEL BY F.M. DOSTOEVSKY’S "THE BROTHERS KARAMAZOV" - Mustafayeva L.V.; Ekabsons A.V. (Galaxy International Interdisciplinary Research Journal, 2024)
This article is devoted to the study and analysis of the literary hero, namely the image of Zosimus in the novel "The Brothers Karamazov" by Fyodor Dostoevsky. The image was considered through the archetype and psychotype, methods of psychological analysis of personality were used for analysis, including the theory of typologies by C.G. Jung and the concept of personality traits by A.E. Lichko.